Convective heat transfer in a lid-driven cavity with a heat-conducting solid backward step under the effect of buoyancy force - Gibanov N. S. Nikita; Sheremet M. A. Mikhail Aleksandrovich; Oztop H. F. Hakan; Al-Salem Kh. Khaled (2017, 2017)
Title screen